2015
DOI: 10.1016/j.ijantimicag.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Earlier switching from intravenous to oral antibiotics owing to electronic reminders

Abstract: Paper-based interventions have been shown to stimulate switching from intravenous (i.v.) to oral (p.o.) antibiotic therapies. Shorter i.v. durations are associated with a lower risk of iatrogenic infections as well as reduced workload and costs. The purpose of this study was to determine whether automated electronic reminders are able to promote earlier switching. In this controlled before-and-after study, an algorithm identified patients who were eligible for i.v.-to-p.o. switch 60h after starting i.v. antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 32 publications
(43 reference statements)
0
5
0
2
Order By: Relevance
“…Beeler et al [ 14 ] performed a prospective, controlled trial using an electronic reminder to stimulate iv-oral switch. Their study resulted in a decrease of total iv duration of 17.5% in the intervention group, and a switch-rate of 26.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beeler et al [ 14 ] performed a prospective, controlled trial using an electronic reminder to stimulate iv-oral switch. Their study resulted in a decrease of total iv duration of 17.5% in the intervention group, and a switch-rate of 26.6%.…”
Section: Discussionmentioning
confidence: 99%
“…This enables antimicrobial stewardship teams to focus on other stewardship activities. The implementation of more sophisticated electronic health record systems (EHRS), which provide electronic alerts, could contribute to an additional reduction of workload [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results should trigger research to examine the influence of this switch on the selection of antimicrobial resistance. A recent investigation in Switzerland has shown that in acute care practice such a switch, leads to a two-step broad spectrum selection pressure, with an oral exposure of predominantly amoxicillin clavulanic acid, and to a lesser extent fluoroquinolones or clindamycine [ 4 ]. This impact on resistance in pathogens and commensals thus is substantial and we therefor plea to examine this in defined case control settings and larger at the population level.…”
Section: Discussionmentioning
confidence: 99%
“…An antimicrobial therapy consists of a specific product, synergies with other agents, its route of administration (formulation), a dose, a treatment interval, treatment duration, and they all can have an effect on the selection of antimicrobial resistance (AMR) [ 4 , 5 ]. A vast amount of studies has been focusing on synergies, the ideal dose (pharmacokinetic/pharmacodynamic parameters [ 6 ]), treatment interval and the impact of duration on resistance [ 7 ], to maintain clinical efficacy while minimizing resistance.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been shown that with a high number of automated CDS messages the likelihood of overriding increases ('alert fatigue'), which bears the risk that providers miss critical notifications [6]. To improve the acceptance and effectiveness of CDS notifications, various approaches have been proposed: -focusing on high-priority DDIs [7] -displaying context information in notifications such as current laboratory values [8] -patient data-driven filtering/suppressing of improper notifications [9] -displaying notifications at the right time, when adverse event becomes likelier [10] -removing notifications when the triggering conditions are no longer met [11] Whereas CDS interventions usually feature only a few of these approaches, we designed a concept hereafter described that combined all features (a-e) to reduce the number of CDS notifications and thereby minimise alert fatigue.…”
Section: Introductionmentioning
confidence: 99%